2016
DOI: 10.1016/j.jbiomech.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage loss patterns within femorotibial contact regions during deep knee bend

Abstract: Osteoarthritis (OA) can alter knee kinematics and stresses. The relationship between cartilage loss in OA and kinematics is unclear, with existing work focusing on static wear and morphology. In this work, femorotibial cartilage maps were coupled with kinematics to investigate the relationship between kinematics and cartilage loss, allowing for more precise treatment and intervention. Cartilage thickness maps were created from healthy and OA subgroups (varus, valgus, and neutral) and mapped to a statistical bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(28 reference statements)
2
6
0
2
Order By: Relevance
“…As the body of research improves, quantifying component placement parameters provides important avenues for more appropriate virtual surgical planning and technology-assisted arthroplasty, especially in patients treated with KA TKA. Comparing the results in this work to previously reported cartilage loss patterns in varus osteoarthritic knees (Johnson & Mahfouz 2016 ; Eckstein et al 2010 ), it is reasonable to presume that the correction of varus deformity in the tibia will result in a larger proximal shift in the P-D level of the medial compartment than a lateral shift (3.6 mm ± 1.1 mm medial vs 1.4 mm ± 1.1 lateral) to account for cartilage and bone loss that is predominantly present in the medial compartment. Eckstein has reported that the central medial tibia compartment and external medial tibial compartment are most susceptible to cartilage loss as osteoarthritis progresses-indicating the predominant change in orientation of the tibial plateau will be an increased varus slope and that the F-E orientation may be less affected by pathological changes (Eckstein et al 2010 ).…”
Section: Discussionsupporting
confidence: 72%
“…As the body of research improves, quantifying component placement parameters provides important avenues for more appropriate virtual surgical planning and technology-assisted arthroplasty, especially in patients treated with KA TKA. Comparing the results in this work to previously reported cartilage loss patterns in varus osteoarthritic knees (Johnson & Mahfouz 2016 ; Eckstein et al 2010 ), it is reasonable to presume that the correction of varus deformity in the tibia will result in a larger proximal shift in the P-D level of the medial compartment than a lateral shift (3.6 mm ± 1.1 mm medial vs 1.4 mm ± 1.1 lateral) to account for cartilage and bone loss that is predominantly present in the medial compartment. Eckstein has reported that the central medial tibia compartment and external medial tibial compartment are most susceptible to cartilage loss as osteoarthritis progresses-indicating the predominant change in orientation of the tibial plateau will be an increased varus slope and that the F-E orientation may be less affected by pathological changes (Eckstein et al 2010 ).…”
Section: Discussionsupporting
confidence: 72%
“…Within this comparison of kinetics and kinematics, we focused on the squat activity, which is similar to everyday activities like sitting down and rising from a seated position, but provides a consistently high joint loading throughout a large range of knee flexion. Therefore, the squat is regularly used to investigate the loaded kinematics of the knee 2629 . The aim of this study was to evaluate whether the medio-lateral (ML) pivot location (in the transverse plane) coincides with the ML distribution of the TF contact force.…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее распространенными осложнениями при ОэКС являются асептическое расшатывание, прогрессирование остеоартроза в смежных отделах сустава, вывих подвижного вкладыша, инфекция, нестабильность, необъяснимая боль после эндопротезирования, перипротезный перелом, износ полиэтилена [54,55]. J.A.…”
Section: обсуждение первой задачи исследованияunclassified